2010
DOI: 10.1016/j.expneurol.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of naloxone on inhibitory pudendal-to-bladder reflex in cats

Abstract: To determine the involvement of opioid receptors in the inhibitory pudendal-to-bladder reflex, the effect of naloxone (0.01–1 mg/kg, i.v.), an opioid receptor antagonist, on the inhibition of bladder activity evoked by pudendal nerve stimulation was investigated in α-chloralose anesthetized cats. The inhibition of reflex isovolumetric bladder contractions induced by pudendal nerve stimulation (5–10 Hz) at intensity threshold (T) for producing complete inhibition was significantly suppressed by naloxone at a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 28 publications
8
47
2
Order By: Relevance
“…Post hoc paired comparisons with Bonferroni correction showed that while normalized bladder pressure was significantly higher with picrotoxin (*P Ͻ 0.001), there was no significant difference between control, paralytic, and washout trials. contributions of opioidergic mechanisms to stimulationevoked bladder inhibition (7,28). The present results reveal that a spinal GABAergic mechanism mediates the inhibitory pudendovesical pathway.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Post hoc paired comparisons with Bonferroni correction showed that while normalized bladder pressure was significantly higher with picrotoxin (*P Ͻ 0.001), there was no significant difference between control, paralytic, and washout trials. contributions of opioidergic mechanisms to stimulationevoked bladder inhibition (7,28). The present results reveal that a spinal GABAergic mechanism mediates the inhibitory pudendovesical pathway.…”
Section: Discussionmentioning
confidence: 52%
“…To block glycinergic receptors, increasing cumulative doses of strychnine (n ϭ 4, 0.01-0.1 mg/kg iv) were administered, including to two animals who received cumulative doses up to 0.25 mg/kg iv (40). Increasing cumulative doses of naloxone (0.1-4.0 mg/kg iv), a competitive opioid antagonist, were administered to identify any opioidergic contribution to bladder inhibition (n ϭ 3), as this was ambiguous from prior studies (7,28).…”
Section: Methodsmentioning
confidence: 99%
“…132 Opioids were also found to contribute to the inhibitory pudendal-to-bladder reflex in cats. 133 In similar experiments, opioids were found to play a differential role in inhibition of nociceptive and non-nociceptive bladder contractions by tibial nerve stimulation. 134 Other experiments have demonstrated that metabotropic glutamate 5 receptors, 135,136 and serotoninergic receptors, 137 which may interact with opioid mechanisms, are involved in bladder inhibition by PNS and that the effects are primarily mediated by spinal, not supraspinal, processes.…”
Section: Coupling Neuromodulation and Pharmacological Therapy For Impmentioning
confidence: 87%
“…The inhibitory pudendal-bladder reflex that promotes bladder storage is thought to be mediated by inhibitory neurotransmitters including glycine, γ-aminobutyric acid, and possibly enkephalins/opioid peptides. Chen et al [15] recently investigated the role of enkephalins in the pudendalbladder reflex by using an opioid receptor antagonist and pudendal nerve stimulation in cats. The researchers remarked that there was an intensity-and frequencydependent effect of pudendal nerve stimulation; a low frequency (5-10 Hz) suppressed isovolumetric bladder contractions, whereas a higher frequency or even lower frequency (1-3 Hz) facilitated bladder contraction, although not consistently.…”
Section: Potential Benefit Of Pudendal Stimulation With Animal and Acmentioning
confidence: 99%
“…The ultimate conclusion was that opioid receptors at least partially contribute to inhibition of reflex bladder activity by pudendal nerve stimulation. When the antagonist was given, the inhibition of reflex bladder activity was reduced, although it could be overcome by increasing the intensity of stimulation [15].…”
Section: Potential Benefit Of Pudendal Stimulation With Animal and Acmentioning
confidence: 99%